Coccolithophore Growth and Calcification in an Acidified Ocean: Insights From Community Earth System Model Simulations. (22nd May 2019) - Krumhardt, K. M.; Lovenduski, N. S.; Long, M. C.; Levy, M.; Lindsay, K.; Moore, J. K.; Nissen, C.
Abstract: Anthropogenic CO2 emissions are inundating the upper ocean, acidifying the water, and altering the habitat for marine phytoplankton. These changes are thought to be particularly influential for calcifying phytoplankton, namely, coccolithophores. Coccolithophores are widespread and account for a substantial portion of open ocean calcification; changes in their abundance, distribution, or level of calcification could have far‐reaching ecological and biogeochemical impacts. Here, we isolate the effects of increasing CO2 on coccolithophores using an explicit coccolithophore phytoplankton functional type parameterization in the Community Earth System Model. Coccolithophore growth and calcification are sensitive to changing aqueous CO2 . While holding circulation constant, we demonstrate that increasing CO2 concentrations cause coccolithophores in most areas to decrease calcium carbonate production relative to growth. However, several oceanic regions show large increases in calcification, such the North Atlantic, Western Pacific, and parts of the Southern Ocean, due to an alleviation of carbon limitation for coccolithophore growth. Global annual calcification is 6% higher under present‐day CO2 levels relative to preindustrial CO2 (1.5 compared to 1.4 Pg C/year). However, under 900 μatm CO2, global annual calcification is 11% lower than under preindustrial CO2 levels (1.2 Pg C/year). Large portions of the ocean show greatly decreased coccolithophore calcification relative to growth, resulting in significant regional carbon export and air‐sea CO2 exchange feedbacks. Our study implies that coccolithophores become more abundant but less calcified as CO2 increases with a tipping point in global calcification (changing from increasing to decreasing calcification relative to preindustrial) at approximately ∼600 μatm CO2 . Plain Language Summary: CO2 emissions from human activity are inundating the upper ocean causing ocean acidification. Coccolithophores, a widespread type of marine algae that make calcium carbonate shells, may be particularly influenced by ocean acidification. In this study we created a phytoplankton‐type representative of coccolithophores in the Community Earth System Model. We performed experiments to explore how ocean acidification from increasing CO2 affects coccolithophore growth and calcification. We found that, as CO2 rises, coccolithophores increase in abundance in several oceanic regions, including the North Atlantic, Western Pacific, and parts of the Southern Ocean, due to a carbon fertilization effect on coccolithophore photosynthesis. However, most areas of the ocean showed decreases in coccolithophore calcification as CO2 increases and ocean acidification becomes more severe. We project that end‐of‐the‐century CO2 concentrations result 11% less oceanic calcification on a global scale relative to preindustrial CO2 levels. Overall, coccolithophores become more abundant in certain regions but are more lightly calcified with increasing CO2 . Key Points: An explicit coccolithophore representation in a major Earth System Model is described Increasing CO2 stimulates coccolithophore growth in certain regions, but calcification is impaired Future CO2 conditions drive a decrease in global marine calcium carbonate production